Whose Culture Is Marketed? Gendered Narratives in Heritage Tourism Promotion in the Borobudur–Prambanan Cultural Region, Indonesia - Muhammad Rehan Sabir; Dewi Candraningrum; Saima Tahir; Alaa Alkhateeb (Indonesian Tourism Journal, 2026)
This study examines how official heritage tourism promotion constructs gendered cultural narratives within the Borobudur–Prambanan cultural region. Heritage tourism promotion is not treated merely as destination marketing, but as a representational arena where cultural identity, historical authority, authenticity, and social visibility are selectively produced. Using a qualitative interpretive design and Critical Discourse Analysis, the study analyzes 87 text–image units from state-linked tourism platforms, including Borobudur, Prambanan, Ramayana Ballet, and Central Java tourism materials. The analysis focuses on seven categories: visibility and invisibility, gender roles, narrative voice, descriptive language, symbolic positioning, agency versus passivity, and cultural authority. The findings reveal that women are frequently visible in promotional images as dancers, artisans, performers, and symbolic markers of tradition, yet their visibility rarely translates into narrative authority. Men, by contrast, are more often associated with historical explanation, institutional voice, ritual legitimacy, and interpretive knowledge. Female-coded cultural practices are commonly commodified through aesthetic spectacle, costume, bodily performance, and emotional atmosphere, while male-coded heritage elements retain intellectual, historical, and spiritual prestige. The study concludes that official heritage tourism promotion reproduces a gendered hierarchy of cultural representation by separating visual presence from cultural authority. More equitable promotional practice requires naming female cultural practitioners, recognizing their knowledge, and presenting women not only as cultural symbols but also as interpreters, transmitters, and authoritative subjects of heritage. This finding highlights the need for heritage tourism institutions to develop more inclusive promotional narratives that acknowledge women’s cultural agency, expertise, and authority in sustaining living heritage traditions.